2021
DOI: 10.1088/1757-899x/1077/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Towards Development of a Web-Based System for Analyzing Marine Ecological Carrying Capacity (MECC) for Managing Marine Resources in The Outer Island of Indonesia (Case Study: Nunukan Regency)

Abstract: Research on the development of data integration system design and web-based system in the calculation of Marine Ecological Carrying Capacity (MECC) for managing marine and coastal resource management has been carried out. In this study, Nunukan Regency, North Kalimantan was chosen as the study area. The process of integrating data in managing marine and coastal resources in a sustainable manner using the carrying capacity concept approach is carried out by designing an information system development system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Any ecosystem that has reached beyond its carrying capacity is unsustainable; empirical evidence has also shown that the ecological carrying capacities of the ocean in China [33], along with many renowned dive sites in Palau [34], Indonesia [35], Malaysia [36], and the Persian Gulf [37] are already overloaded. Ecological carrying capacity is an indicator that is widely used in the environmental management of recreational activities.…”
Section: Introductionmentioning
confidence: 99%
“…Any ecosystem that has reached beyond its carrying capacity is unsustainable; empirical evidence has also shown that the ecological carrying capacities of the ocean in China [33], along with many renowned dive sites in Palau [34], Indonesia [35], Malaysia [36], and the Persian Gulf [37] are already overloaded. Ecological carrying capacity is an indicator that is widely used in the environmental management of recreational activities.…”
Section: Introductionmentioning
confidence: 99%